EFFECT OF MAGGOT (BLACK SOLDIER FLY) MEAL ADDITION IN RATIONS ON COMMERCIAL CUTS OF BROILER CARCASSES - I G. D., Yasa; Sudiastra, I W.; Candrawati, D. P. M. A. (Jurnal Peternakan Tropika, 2024)
This study aims to determine the effect of the addition of maggot flour (Black Soldier Fly) in the ration on commercial cuts of broiler carcasses. The research was conducted in Tengkudak Village, Penebel District, Tabanan Regency, Bali for 2 months. This study used a completely randomized design (CRD) with four treatments and four replications. Each experimental unit was filled with four broilers with a homogeneous body weight range. The four treatments consisted of P0 (without the addition of maggot flour as control), P1 (ration with the addition of 3% maggot flour), P2 (ration with the addition of 6% maggot flour) and P3 (ration with the addition of 9% maggot flour). The observed variables were slaughter weight, carcass percentage, back percentage, chest percentage, thigh percentage and wing percentage. The results showed that broilers treated with P2 and P3 did not significantly increase (P>0.05) slaughter weight compared to P0. P1 treatment significantly decreased (P <0.05) cutting weight compared to P2 and P3. In the variable percentage of carcass, percentage of back, percentage of chest, percentage of thigh and percentage of wings, P1, P2 and P3 treatments were not significantly different (P>0.05) compared to P0. The conclusion of this study is the addition of maggot flour (Black Soldier Fly) in broiler rations up to 9% can increase slaughter weight and carcass percentage, back percentage, chest percentage, thigh percentage and wing percentage similar to broilers fed commercial rations without the addition of maggot flour.